IMPACT OF INTERNATIONAL STANDARDS IN THE LEGAL REGULATION OF WORKING HOUR S IN THE REPUBLIC OF UZBEKISTAN - Yusupov Nodirbek Abdujalilovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses in detail the issues of legal regulation of working time using international standards (UN, ILO), as well as the impact of international standards on the labor legislation of the Republic of Uzbekistan in the field of legal regulation of working time. The issues of compliance of working hours with international standards, establishment of normal working hours, part time work, night work and overtime work were considered.